Control, Learning, and Resistance - Michael Newman (Adult Education Research Conference, 2000)
This paper argues that learning can be a tool for social and political change. It proposes a theoretical framework for educators and learners living out part or all of their lives in struggle. And it examines a moral dilemma for educators who see learning as indivisible from action.